1985
DOI: 10.1099/0022-1317-66-2-351
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Sequence Homology between Double-stranded RNA from European and American Hypovirulent Strains of Endothia parasitica

Abstract: SUMMARYDot blots of dsRNA from European and American hypovirulent (H) strains of the chestnut blight fungus, Endothia parasitica, were hybridized with 32p-5'-end-labelled fragments of denatured dsRNA of French, Italian and American origins. Although dsRNA from European or American strains reacted well with labelled RNA probes from strains from the same continent there was little or no cross-hybridization between RNA from strains from different continents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Unfortunately, records identifying exactly which strains were released are incomplete, and the investigators involved are not available (S. L. Anagnostakis, personal communication). Previous studies regarding the interrelatedness of dsRNAs from C. parasitica indicated that dsRNAs from European strains are related to one another, and dsRNAs from several North American strains are related to one another, but that dsRNAs from European strains are not closely related to those from North American strains (L'Hostis et al, 1985 ;Paul et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, records identifying exactly which strains were released are incomplete, and the investigators involved are not available (S. L. Anagnostakis, personal communication). Previous studies regarding the interrelatedness of dsRNAs from C. parasitica indicated that dsRNAs from European strains are related to one another, and dsRNAs from several North American strains are related to one another, but that dsRNAs from European strains are not closely related to those from North American strains (L'Hostis et al, 1985 ;Paul et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The dsRNA virus-like elements associated with different hypovirulent strains of C. parasitica exhibit considerable heterogeneity with respect to genome size, number of dsRNA species, genome concentration, and sequence homology (20,31,34 been sequenced (45,46). The largest dsRNA contains two open reading frames (ORFs) which encode polyproteins that proteolytically process themselves (12,13,46,47).…”
mentioning
confidence: 99%
“…The phenomenon of cytoplasmically transmissible hypovirulence in C. parasitica is one of the best-documented examples of a naturally occurring form of biological control for plant disease. Our studies are directed towards understanding how dsRNA genetic elements in the fungus cause the attendant changes in host phenotype.The dsRNA virus-like elements associated with different hypovirulent strains of C. parasitica exhibit considerable heterogeneity with respect to genome size, number of dsRNA species, genome concentration, and sequence homology (20,31,34 (12,13,46,47). A structural resemblance between hypovirulence-associated dsRNAs and replicative forms of positive-strand RNA virus genomes has been noted (12,22,29,46,51).…”
mentioning
confidence: 99%
“…Subsequent studies showed that the hypovirulence phenotype was transmissible by hyphal fusion to virulent strains (1,2,5,6 Correlative evidence strongly suggests that doublestranded RNA (ds RNA) is the cytoplasmic transmissible determinant responsible for hypovirulence in E. parasitica (9)(10)(11). ds RNAs associated with different hypovirulent strains vary with respect to size, concentration, and sequence homology (3,(9)(10)(11)(12). Information concerning the relationship of these ds RNAs to each other, their structural organization, and their role in hypovirulence is limited or nonexistent.…”
mentioning
confidence: 99%